Testing, Piloting, and Validation of the Rural Water Indicator Global Framework in the African Context - Banks, Brian; Mendez-Castillo, Ethel; Vargas-Ramirez, Miguel; Zimmermann, Sabrina; Loughnan, Libbet (World Bank, Washington, DC, 2020)
This document presents the findings of the pilot conducted in Burkina Faso, Kenya, and Sierra Leone to determine the feasibility and utility of the indicators proposed by the World Bank in the Rural Water Metrics Global Framework. Through standard indicators, the proposed framework aims to facilitate improvements in national and global reporting and analysis, which would improve rural water services around the world. This document provides background on the framework; shows how it relates to other efforts to harmonize rural water data; and outlines development of the framework. It also describes the pilot—its methodology, findings, and limitations—and offers recommendations regarding the indicators themselves; suggests an implementation approach; and proposes a pathway for collection of the data using integration into national monitoring framework.